2017
DOI: 10.1007/s12325-017-0527-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Patterns and Early Outcomes of ALK-Positive Non-Small Cell Lung Cancer Patients Receiving Ceritinib: A Chart Review Study

Abstract: Novartis Pharmaceutical Corporation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 19 publications
4
23
1
Order By: Relevance
“…Similar to results from previously conducted studies of real-world treatment patterns for ALK+ NSCLC [25,26,[36][37][38][39], we found that crizotinib was the most commonly prescribed first-line ALK TKI therapy in clinical practice. In the second-line ALK TKI setting (post crizotinib), our results showed that ceritinib was the most commonly prescribed therapy, which is consistent with the approval timelines and similar to the results of other real-world studies [24,25,[37][38][39][40][41][42]. These results are not surprising, as crizotinib was initially approved by the FDA in 2011 and was the first commercially available ALK TKI therapy in the U.S. [43].…”
Section: Discussionsupporting
confidence: 88%
“…Similar to results from previously conducted studies of real-world treatment patterns for ALK+ NSCLC [25,26,[36][37][38][39], we found that crizotinib was the most commonly prescribed first-line ALK TKI therapy in clinical practice. In the second-line ALK TKI setting (post crizotinib), our results showed that ceritinib was the most commonly prescribed therapy, which is consistent with the approval timelines and similar to the results of other real-world studies [24,25,[37][38][39][40][41][42]. These results are not surprising, as crizotinib was initially approved by the FDA in 2011 and was the first commercially available ALK TKI therapy in the U.S. [43].…”
Section: Discussionsupporting
confidence: 88%
“…Din et al reported that crizotinib showed a 1 year survival rate of 71.2% and an objective response rate of 70.9% [34]. Bendaly et al reported that the ORR for ceritinib was 69% and median PFS was 12.9 months [6]. In a large, multi-country medical chart review (n = 1471) with seven countries, there was a significant improvement in complete response (odds ratio (OR), 2.65; 95% CI, 1.69-4.15) and a significant reduction in recurrence/progression (OR, 0.38; 95% CI, 0.24-0.59) [35].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…One of them is crizotinib, initially designed for a mesenchymal-epithelial transition factor (MET) inhibitor in 2007, which prompted the development of anaplastic lymphoma kinase (ALK) target therapy [5]. It became the first ALK inhibitor to be approved by the Food and Drug Administration (FDA) in 2011 for standard first-line therapy in ALK-positive NSCLC, which accounts for approximately 2-7% of patients diagnosed with NSCLC [6]. However, the progression of brain metastases and resistance were the biggest challenges during crizotinib treatment [7].…”
Section: Introductionmentioning
confidence: 99%
“…97 It is worth noting that ceritinib may be highly effective in patients whose disease has progressed on crizotinib and has metastasized regardless of where the metastatic site is. 100…”
Section: Ceritinibmentioning
confidence: 99%